Transient Electro-Graphitization of MOFs Affecting the Crystallization of Ruthenium Nanoclusters for Highly Efficient Hydrogen Evolution - Karim, Golam Masud; Patra, Amalika; Deb, Sujit Kumar; Upadhya, Hemanta; Das, Snehasish; Mukherjee, Priyam; Ahmad, Waleed; Barman, Narad; Thapa, Ranjit; Dambhare, Neha, V; Rath, Arup Kumar; Das, Jaysri; et al. (John Wiley & Sons Ltd., 2024)
Fine control over the graphitization level of carbonized nanostructures can play a strategic role in tuning the crystallization of supported nanocatalysts, thereby modulating the kinetics of catalysis. However, realizing the synergistic interplay of graphitization-tunable support and supported catalysts poses a significant challenge. This study proposes a current pulse-induced ultrafast strategy for developing MOF-derived graphitic nano-leaves (GNL) and supported ultrafine ruthenium nanoclusters exhibiting selective crystallization states depending on the tunable graphitization level of GNL. The resulting ultrafine (approximate to 0.7 nm) amorphous-ruthenium nanoclusters linked with GNL (a-Ru@GNL500) exhibit state-of-the-art performance in the hydrogen evolution reaction (HER), requiring very low overpotentials of only 23.0 and 285.0 mV to achieve current densities of 10 and 500 mA cm-2, respectively. Furthermore, a-Ru@GNL500 demonstrates exceptional operational stability for 100 h under high HER currents of 200 and 400 mA cm-2. Density functional theory reveals that the unique electronic structure of a-Ru and the cooperative effect of cobalt embedded in the graphitic layer lower the occupancy of the antibonding orbital, resulting in an accelerated HER process. Additionally, the unique electronic structure, highly conducting GNL, and efficient bubble release dynamics of super-aerophobic a-Ru@GNL500 contribute to reduced overpotentials, particularly at high HER current densities. Adjusting graphitization in MOF-derived carbon nano-leaves during a 2-stage current pulse-induced process enables the creation of ruthenium nanoclusters with precise dispersion and customizable crystallization (single atom, amorphous/crystalline). The refined amorphous ruthenium-linked nano-leaves demonstrated outstanding hydrogen evolution reaction (HER) activity (10 mA cm-2 @ 23 mV) and remarkable stability under high current densities, attributed to electronic synergies and ultralow bubble adhesion. image